Using evidence how research can inform public services - Nutley, Sandra M.; Walter, Isabel; Davies, Huw T. O. 1961- (Policy Press, 2007)
'Using Evidence' provides a multidisciplinary framework for understanding the research use agenda. The book considers how research use & the impact of research can be assessed. It is useful for university & government researchers, research funding bodies, public service managers & professionals, & students of public policy & management.
Includes bibliographical references (p. 321 - 354) and index
Keywords: Beleidsonderzoek; Openbare dienstverlening; Overheidsbeleid; Politik; Public administration -- Great Britain; Political planning -- Great Britain; Öffentlicher Dienst; Politische Planung; Forschung; Großbritannien